Memetakan Skala Prioritas Kebijakan Penanganan Pandemi Covid-19 Perspektif Maqa?s?id al-Syari?’ah: Analisis terhadap Peraturan Perundang-Undangan di Indonesia: Memetakan Skala Prioritas Kebijakan Penanganan Pandemi Covid-19 Perspektif Maqa?s?id al-Syari?’ah: Analisis terhadap Peraturan Perundang-Undangan di Indonesia - Rozi, Masykur (Journal of Islamic Law, 2021)
The handling of the Covid-19 pandemic in Indonesia still has not shown significant results. It can be seen that the data shows that throughout almost a year of the pandemic has not been a decline in positive confirmed numbers. Many policies have been enacted as the basis for such handling. This article examines the priority scale and repositioning its priority in light of the maqāṣid asy-sayarī’ah perspective. The author uses ḍarūriyyāt khamsah as a method of mapping priorities through its conceptual framework. As for the operational function, the author borrows William N. Dunn’s theory of public policy arguments. The genre used is analysis for policy, wrapped in a qualitative approach using documentative data on the policy material manifested in Perppu Number 1 the Year 2020. This theoretical convergence makes ḍarūriyyāt khamsah an information base in finding and interpreting data, qualifications in objection, warrant, rebuttal, and backing. After seeing the priority, it will be used as a policy claim. After applying it to the policy, it can be concluded that the policy divides the pandemic dimension into two, namely health and its effects. Meanwhile, in the effort to handle them, both are not responded with proportional values. The government has prioritized managing its effects over health un from the perspective of ḍarūriyyāt khamsah, and health care should be given top priority because Covid-19 threatens lives directly. In contrast, the threat of pandemic effects threatens indirectly. The health agent is wasīlah ḍarūriyyah, while wasīlah handling pandemic effects is ḥājiyyah. This situation can change depending on the conditions in the field.